A Systematic Narrative Review : Kajian Farmakologi dan Toksikologi Meniran (Phyllanthus niruri L.): A Systematic Narrative Review : Pharmacology and Toxicology Study of Meniran (Phyllanthus niruri L.) - Pandapotan, Herianto; Fitriani, Hannie; Hayati, Farida; Syukri, Yandi (Media Farmasi, 2025)
Background: Meniran (Phyllanthus niruri L.) is a traditional medicinal plant widely utilized in various countries due to its pharmacological potential. Objective: This study aims to explore the biological activity by summarizing scientific findings regarding the pharmacological effects and toxicological profile of meniran, as well as highlighting the understanding related to safe therapeutic doses. Methods: This review was conducted using a systematic narrative approach, utilizing literature from journal articles, scientific reports, reference books, and publication data from databases such as PubMed, Scopus, and Google Scholar. Inclusion criteria comprised peer-reviewed studies published in the last 10 years, while exclusion criteria eliminated non-scientific articles and those not relevant to pharmacology or toxicology. Results: A total of 200 articles were identified, resulting in 34 articles selected for review after applying inclusion and exclusion criteria. From the four journals/studies reviewed, it was found that bioactive compounds in meniran, such as flavonoids and lignans, play a crucial role in therapeutic effects including antioxidant activity, hepatoprotection, antimicrobial effects, and anti-inflammatory properties. Additionally, two journals/studies indicated that long-term use of meniran may have toxic effects. Conclusion: Meniran exhibits pharmacological activities such as antioxidant effects, hepatoprotection, antimicrobial effects, and anti-inflammatory effects; however, it may have toxic effects on the kidneys and liver when used in high doses. Further research is necessary to ensure the safety and effectiveness of its use in medical therapy.